Efficacy and cardiac safety of the concurrent use of trastuzumab and anthracycline-based neoadjuvant chemotherapy for HER2-positive breast cancer: a systematic review and meta-analysis - Wu Y; Xu Z; Zhang K; Wu J; Li X; Arshad B; Li Y; Wang Z; Li H; Wu K; Kong L (Dove Medical Press, 2018)
Yu-Tuan Wu,1,* Zhou Xu,1,* Ke Zhang,2,* Jiu-song Wu,3,* Xin Li,1,* Bilal Arshad,1 Ying-Cun Li,3 Zhong-Liang Wang,2 Hong-Yuan Li,1 Kai-Nan Wu,1 Ling-Quan Kong1 1Department of Endocrine and Breast Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, China; 2Department of Orthopedics, Children’s Hospital of Chongqing Medical University, Chongqing 400020, China; 3Department of General Surgery, Children’s Hospital of Chongqing Medical University, Chongqing 400020, China *These authors contributed equally to this work Abstract: The concurrent use of trastuzumab and anthracycline-based neoadjuvant chemotherapy (NAC) has been proposed to improve the pathologic complete response (pCR) rate, although there are conflicting views about its efficacy and safety. The purpose of this study was to evaluate the efficacy and cardiac safety of the concurrent use of trastuzumab and anthracycline-based NAC for human epidermal growth factor receptor 2 (HER2)-positive locally advanced breast cancer. We systematically searched PubMed, Embase, and Cochrane databases from inception until July 1, 2017, for relevant articles. A total of 13 studies were included in the meta-analysis. The results showed that the pCR rate was significantly higher in the concurrent use of trastuzumab and anthracycline group (45%) than that in the nonconcurrent use group (32%) (OR: 2.36, 95% CI: 1.69–3.30, P<0.0001). Besides, the pooled absolute rate of breast conservation surgery (BCS) was 48% (95% CI: 0.35–0.61) and 38% (95% CI: 0.14–0.62) in the experimental and control groups, respectively (OR: 1.10, 95% CI: 0.64–1.90, P=0.73). No significant differences were found in the left ventricular ejection fraction (LVEF), which decreased by >10% (OR: 1.26, 95% CI: 0.55–2.88, P=0.59), and in terms of cardiac failure (OR: 2.17, 95% CI: 0.24–19.84, P=0.49), when comparing the concurrent use of trastuzumab and anthracyclines with their nonconcurrent use. In conclusion, the concurrent use of trastuzumab and anthracycline-based NAC for certain HER2-positive locally advanced breast cancers significantly improves the pCR rates without obvious increases in the cardiotoxicity. Keywords: breast cancer, HER2, neoadjuvant chemotherapy, trastuzumab, anthracycline